Exam Time Usage in Accounting Courses and Student Exam Performance - Xiang, Meifang (Journal of Accounting and Finance, 2023)
The study examines the relationship between student time usage during accounting exams and their exam performance. The results show that exam time usage does not have a significant impact on accounting student exam performance. However, the current study provides evidence that GPA has a significant effect on accounting student exam performance. In addition, the current study examines the possible factors that may affect a student’s decision in the length of the exam time. The results also show that GPA and whether students have taken high school accounting courses are two significant factors: Students with a better GPA and/or students who have had high school accounting courses are likely to use more exam time than their peers.